Higher Education in the New Era - Habib, Habibullah (Advances in Social Sciences Research Journal, 2019)
Learning and changing have eternal bilateral crucial relation with each other. Today’s education, especially higher education depends on social equality, economic stability, peacefulness, and good environmental situation. In comparison with the World Declaration on higher education (1998), for our current century Higher education is facing a number of basic important challenges at the local, regional and worldwide (international) level. Currently, globalization is a multifaceted movement that strongly depends on social, economic, cultural, environmental and political implication for higher education. In some countries, the phenomenon of globalization has brought out opportunities and posed the country numerous challenges for the few years in the future. World as a global village not be constrained by national boundaries, it is combined with new technology, media, Trade, and travel. Higher education in the new era an irreversible process that has comprehensive influence role 0n global society, thus our new era strongly needs to provide progressive trends for the new higher education that, should responsible for the demands and new market, because modern knowledge industries encourage many quantities of higher education institutions to participate in competition for obtaining resources and customers.